Carbon taxes and industrial competitiveness: evidence from energy-intensive industries in the Nordic region - Ridwan, Mohammad; Antor, Zulfiquar Ali; Ko, Jeremy; Akther, Afsana; Leung, Chun Kai; Ming, Wai-Kit (Frontiers in Sustainability, 2026)
The key question for open economies is how to maintain ambitious climate policy while remaining competitive in the industrial sector. Carbon taxes have been accused of increasing production costs while being a driver of efficiency and innovation. The Nordic region offers a severe experiment on this argument, as it has the highest carbon prices globally and depends highly on manufacturing exports. This study examines the relationships among carbon taxation, energy consumption, and industrial competitiveness in Nordic economies from 2000-2024. We estimate the joint effect of environmental policies and structural factors on export performance via panel econometric techniques. To examine this relationship, the study used quantile regression, panel-corrected standard errors, Driscoll–Kraay standard errors, the system generalized method of moments, and panel autoregressive distributive lag model. The results indicate that carbon taxation improves manufacturing exports, implying that tougher climate policies can reinforce competitiveness via induced innovation and efficiency improvements. Exports are boosted by fossil fuel consumption and negatively affect electricity consumption, GDP per capita, and carbon intensity. Value-added manufacturing enhances competitiveness, whereby industrial upgrading and involvement in global value chains have their place. Causality tests revealed a two-way relationship between carbon taxes and exports, and robustness tests confirmed the consistency of the findings. However, the GMM establishes weaker effects of taxation and value added. This study provides evidence that climate leadership and trade competitiveness are not mutually exclusive. Nordic economies demonstrate a viable path to sustainable competitiveness in the global low-carbon transition through carbon pricing within coherent policies supporting innovation, energy efficiency, and low-carbon strategies.